Vulnerabilities of Prostate Glandular Concretions Considered as Artefacts: A Cross-sectional Biopsy Slide Study - Surraj SUSAI; Rohini MOTWANI; Mrudula CHANDRUPATLA (Medeniyet Medical Journal)
Objective: There is no clear consensus regarding the contour of prostatic glandular intraluminal concretions. This study enlightens the rational approach toward deciphering the true nature of these concretions and evaluates their role in normal routine histology of the prostate gland. Methods: Fifty hematoxylin and eosin slides that were prepared from procured transrectal biopsy specimens of normal prostate glands from asymptomatic patients suspected of having a prostatic disease but later found to be normal were retrospectively observed for the staining, contour, and positioning of the aggregated masses or concretions within their prostatic lumina and were then compared with the blood prostate specific antigen (PSA) levels. Results: Although significant associations highlighting the utility of these masses in presumed pathological states of the gland were drawn by comparing their staining parameters and contours to those of their respective PSA levels, their interluminal contour variations and vivid staining appearances did not necessarily rule out the possibility of some of them being artefacts, provided they were assessed in totality with the surrounding acini. Intensely eosinophilic concretions were found in patients with a high mean age and those with high PSA levels. Conclusions: Prostatic intraluminal masses that were rounded tended to indicate pathological shifts within the gland; however, the possibility of them changing to artefacts during slide preparations could not be ruled out.